Biotechnological valorization of mycelium-bound lipase of Penicillium purpurogenum in hydrolysis of high content lauric acid vegetable oils - de Castro, Tarsila F.; Cortez, Daniela V.; Gonçalves, Daniel B.; Bento, Heitor B.S. [UNESP]; Gonçalves, Rhyan L.N.; Costa-Silva, Tales A.; Gambarato, Bruno C.; de Castro, Heizir F.; de Carvalho, Ana Karine F. (Elsevier, 2022)
The study deals with the direct use of whole cells of a species of Penicillium as biocatalyst (mycelium-bound lipase) for the hydrolysis of vegetable oils under low-power ultrasonic irradiation. Whole cells of Penicillium purpurogenum with lauric acid-specificity lipase were able to hydrolyze vegetable oils with high content of this fatty acid. Up to 90% hydrolysis values were reached at 7 h of reaction, providing high fatty acid contents in shorter times concerning the literature. The results suggest that the ultrasound wave improves the interfacial area and that the lipase of Penicillium purpurogenum is bound to the cell, in a place with easy access to the substrate. On the other hand, the presence in the substrate of fatty acids with 18 carbons (stearic, oleic, and linoleic) in a concentration greater than 20%, negatively interferes with the degree of hydrolysis, indicating a possible limitation of lipase specificity. The present study highlights the biotechnological potential of mycelium-bound lipase (naturally immobilized enzymes) for use in the hydrolysis of babassu, coconut and kernel oils, which are not directly integrated into the food production chain.
Keywords: Biomass valorization; Hydrolysis; Lauric acid; Mycelium-bound lipase; Penicillium purpurogenum